Remote video auditing in the endoscopy unit for evaluation of duodenoscope reprocessing in a tertiary care center - Raphael, Kara L.; McNoble, Ellen; Goldbeck, Jessica; Stiles, Megan; Miller, Larry S.; Trindade, Arvind J. (Endoscopy, 2020)
Background A significant proportion of duodenoscope-transmitted infections have resulted from errors related to reprocessing. Remote video auditing (RVA) is a tool that can monitor reprocessing compliance but it has not been previously evaluated in a tertiary care setting. The aims of this study were to evaluate: 1) RVA feasibility in a tertiary care setting (defined as the ability to audit every step of duodenoscope reprocessing without delaying the next procedure due to unavailability of duodenoscopes); and 2) the use of RVA as a compliance monitoring tool.Methods This was a prospective study at a tertiary care center. A video camera with offsite monitoring was installed in March 2018. Auditors delivered a compliance score after each procedure. The duodenoscope was not used until it passed the audit. Feasibility and compliance data were collected from April 2018 to August 2019 after a 1-month run-in phase. Both per-step compliance and overall 100 % compliance rates were measured.Results Of 743 duodenoscope reprocessing procedures, 32 666 individual steps were audited and 99.9 % of the steps were fully viewable. The mean time per audit was 38.3 minutes, the mean duodenoscope turnover time was 76.1 minutes, and there were no delays to the next procedure due to unavailability of duodenoscopes. The per-step compliance rate was 99.5 % but the overall 100 % compliance rate was 90.3 %.Conclusions The use of RVA in duodenoscope reprocessing was feasible and promoted sustained high-level compliance in a tertiary care center.